2019
DOI: 10.1029/2019jf005081
|View full text |Cite
|
Sign up to set email alerts
|

A Well‐Posed Alternative to the Hirano Active Layer Model for Rivers With Mixed‐Size Sediment

Abstract: The active layer model (Hirano, 1971) is frequently used for modeling mixed‐size sediment river morphodynamic processes. It assumes that all the dynamics of the bed surface are captured by a homogeneous top layer that interacts with the flow. Although successful in reproducing a wide range of phenomena, it has two problems: (1) It may become mathematically ill‐posed, which causes the model to lose its predictive capabilities, and (2) it does not capture dispersion of tracer sediment. We extend the active layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 147 publications
(303 reference statements)
0
12
0
Order By: Relevance
“…This allows for solving the hydrodynamic and morphodynamic equations consecutively instead of simultaneously. It has been shown that such decoupling of the equations is acceptable for values of the Froude number smaller than 0.7 approximately (Chavarrías et al., 2019; De Vries, 1965; Lyn, 1987; Lyn & Altinakar, 2002), which is typically considered a valid approximation for lowland rivers.…”
Section: The Proposed Methods (Vs the Traditional Monte Carlo Method)mentioning
confidence: 99%
“…This allows for solving the hydrodynamic and morphodynamic equations consecutively instead of simultaneously. It has been shown that such decoupling of the equations is acceptable for values of the Froude number smaller than 0.7 approximately (Chavarrías et al., 2019; De Vries, 1965; Lyn, 1987; Lyn & Altinakar, 2002), which is typically considered a valid approximation for lowland rivers.…”
Section: The Proposed Methods (Vs the Traditional Monte Carlo Method)mentioning
confidence: 99%
“…For the current model, it turns out that both the bed level Journal of Geophysical Research: Earth Surface 10.1029/2019JF005430 and the sorting properties are not affected by a decreasing grid size (and time step), such that we are confident that the presented results are physically correct. As an alternative to our employed method, recent advancements have resulted in approaches (e.g., the SILKE model Chavarrías et al, 2019) that ensure the well posedness of the active layer concept.…”
Section: Assumptions and Limitationsmentioning
confidence: 99%
“…Under certain conditions the active layer model may become ill-posed (Ribberink, 1987;Stecca et al, 2014;Chavarrías et al, 2018). In these ill-posed situations, short-wavelength perturbations may be triggered (by for instance numerical noise) and grow until a point where the mathematical problem becomes well-posed again.…”
mentioning
confidence: 99%
“…In a practical sense, these oscillations lead to changes of the strati ed bed which are physically not valid. According to Chavarrías et al (2018), it is typical for ill-posed problems that ner grids result in larger errors since the erroneous perturbations have more space to grow, whereas solutions of well-posed problems converge with decreasing grid size. For the current model, it turns out that both the bed level and the sorting properties are not a ected by a decreasing grid size (and time step), such that we are con dent that the presented results are physically correct.…”
mentioning
confidence: 99%
See 1 more Smart Citation